(untitled) (Revista de Medicina Clinica, 2023)
Paradoxical embolism refers to the passage into the arterial circulation of a venous thrombus located in the right heart chambers through a heart defect, usually located in the interatrial septum. The most common heart defect is patent foramen ovale. We present a case of a 63-year-old man who debuted with a paradoxical embolism in order to review its diagnosis and treatment.